The effects of diagenesis on the trace element and stable isotope geochemistry of non-marine ostracod valves - Keatings, KW; Heaton, THE; Holmes, JA (KLUWER ACADEMIC PUBL, 2002)
The trace-element and stable-isotope geochemistry of non-marine ostracod valves is a valuable tool in palaeolimnology. However, the potential effects of early diagenesis on geochemical composition are poorly documented. In this study, the effect of partial dissolution on the trace-element (Sr and Mg) and isotopic (O-18/O-16 and C-13/C-12) composition of late Quaternary non-marine ostracod valves was investigated. Both unaltered and extremely degraded valves of the species Cypretta brevisaepta recovered from the same core level had trace-element and stable-isotope ratios that were drawn from the same statistical population, suggesting that the geochemical effects of early diagenesis are minimal. However, since the possibility remains that diagenesis could under certain circumstances alter valve chemistry, only valves in pristine condition should be used in palaeoenvironmental studies whenever feasible.